Interactive E-Book Model Based on Local Wisdom as a Media for Learning Exposition Text Reading Skills - Afnita Afnita; Ahmad Husein; Ridha Hasnul Ulya (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
This study aims describes the process of designing an interactive e-book model based on the local wisdom of Minangkabau culture. This type of research is mixed methods or commonly known as mixed research methods. The mixed model used is a 4-D model consisting of four stages, namely define, design, develop, and disseminate. This research was conducted on students of class X of State High School 2 Padang. Innovative learning media are indispensable by students to be used independently in the learning process Indonesian. Therefore, research in interactive e-book models is used as one of the alternatives to overcome the limitations of learning media in exposition text reading skills. The results of this study describe the making of an interactive e-book model based on local wisdom of exposition text reading skills with a validity value of 94.44% with a very valid category. Based on the feasibility aspect of content obtained validity value of 97.50% with a very valid category. Based on the aspect of eligibility of validity, obtained a validity value of 89.28% with a very valid category. Based on the results of the study, it can be concluded that the interactive e-book for reading skills reading the exposition text of students of class X is valid and can be continued to the next stage.